Al-Taḥlīl al-Taqābulī Bayn al-Lugah al-ʽArabiyah wa al-Lugah al-Injlīziyah ʽalā Mustawā al-Tafḍīl - Wahidah Wahidah (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2020)
Language is the most important thing in human life. Each language has different rules. Like Arabic and English. In this regard, the researcher is interested in discussing the contrastive analysis between Arabic and English, using the isim tafdlil in Arabic and the degree of comparison in English as the object of his research. The researcher uses a contrastive analysis method, with a descriptive approach. That is by comparing Arabic and English and predicting difficulties that may arise in learning the two languages and using linguistics as a tool of analysis. The conclusion of the article is very important to study because it will greatly help the academic community and make it easier for students to understand one of the important language forms, namely isim tafdlil or prepositional level, both in Arabic and English.